The forbidden door [compact disc, unabridged] : a Jane Hawk novel - Koontz, Dean R. (Dean Ray), 1945- (Koontz, Dean R. (Dean Ray), 1945- Jane Hawk novel.)
Jane Hawk thinks her precious five-year-old son is hidden safely away, with vigilant, indomitable friends. But the malice and resources of her powerful adversaries are boundless and their hunters are circling ever closer to the boy, hoping to draw his mother into their trap. Jane's courage, wits, discipline, and skill will be tested as never before, as she searches for a way through an ever-contracting labyrinth of terror.